30 Rock - Season 2 Episode 1-15 - Scardino, Don; Engler, Michael; Mancuso, Gail; Cernjul, Vanja; Clark, Matthew; Fey, Tina; Baldwin, Alec; Morgan, Tracy (Universal Pictures, 2016)
After taking home the 2007 Emmy for Outstanding Comedy Series, "30 Rock" returned for its sophomore season with an even sharper satirical tool set, skewering everything from reality television (hello, Milf Island) to the suit & tie shenanigans of its own network. Set behind the scenes at "The Girlie Show", a fictional sketch comedy series, 30 Rock follows show runner Liz Lemon (Tina Fey) as she contends with her program's flighty stars, Tracy Jordan (Tracy Morgan) and Jenna Maroney (Jane Krakowski), and runs interference between network exec Jack Donaghy (Alec Baldwin) and her own unruly writing staff. This season starts off as TGS returns from summer hiatus, and gets straight to the hilarious disasters; over the course of 15 episodes, Liz tries (and fails) to buy a condo, Jack has a scandalous love affair with a liberal, and Kenneth (Jack McBrayer), the excitable page, accidentally throws an alcohol-soaked rager. This collection contains every moment from the delightfully absurd and highly quotable 2007-2008 season, featuring guest appearances from Jerry Seinfeld, Edie Falco, and David Schwimmer. [www.amazon.co.uk]